Demographic Patterns of Cumulative Arrest Prevalence by Ages 18 and 23. (April 2014) - Brame, Robert; Bushway, Shawn D.; Paternoster, Ray; Turner, Michael G.
In this study, we examine race, sex, and self-reported arrest histories (excluding arrests for minor traffic violations) from the National Longitudinal Survey of Youth 1997 (NLSY97; N = 7, 335) for the period 1997 through 2008 covering cumulative arrest histories through ages 18 and 23. The analysis produces three key findings: (a) males have higher cumulative prevalence of arrest than females and (b) there are important race differences in the probability of arrest for males but not for females. Assuming that the missing cases are missing at random (MAR), about 30% of Black males have experienced at least one arrest by age 18 (vs. about 22% for White males); by age 23 about 49% of Black males have been arrested (vs. about 38% for White males). Earlier research using the NLSY97 showed that the risk of arrest by age 23 was 30%, with nonresponse bounds [25.3%, 41.4%]. This study indicates that the risk of arrest is not evenly distributed across the population. Future research should focus on the identification and management of collateral risks that often accompany arrest experiences.